Sintasan Spora Bacillus cereus selama Pengolahan dan Penyimpanan Rendang - Fadhina, Maisharah; Nuraida, Lilis; Dewanti-Hariyadi, Ratih (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Bacillus cereus is a heat-resistant spore-forming bacterium that has been linked to outbreaks of foodborne illnesses. Rendang is a traditional Indonesian food made from beef heated in coconut milk and seasoning consisting of various kinds of spices (bumbu rendang) which is thought to inhibit germination of bacterial spores. This research aimed to determine the fate of B. cereus spores during heating and storage of rendang. Spores of B. cereus were inoculated into rendang mixture (beef, bumbu rendang, coconut milk) and control (beef and coconut milk) to achieve a spore concentration of 5 log CFU/g. Rendang mixture or control was heated for 6 h to produce rendang with water content of 35.77% (db) and aw of 0.90. For storage study, rendang after heating was inoculated with 5 log CFU/g spores and stored at room temperature for 4 days. The number of total bacteria and spores was enumerated using total plate count (TPC) method. The number of B. cereus spores decreased during heating in rendang and control, but the decrease rate was slightly faster in rendang than that in control. At the end of heating, spores were reduced by 5 log cycles to <1 log CFU/g in rendang and control. The number of B. cereus spores in rendang and control decreased insignificantly during storage at room temperature. However, the total number of B. cereus in control showed an increase, suggesting possible germination, which was not observed in rendang. This research suggests that spices in bumbu rendang may contribute to inactivation of B. cereus spores during heating and inhibition of their germination during storage.